Development of a blocking ELISA employing a VP1-specific monoclonal antibody for the detection of DHAV3 antibodies - Cuiping Song; Tianyuan Li; Jing Wang; Peidong Guo; Wenjing Yang; Ning Tang; Yang Qu; Siyu Li; Xusheng Qiu; Lei Tan; Yingjie Sun; Ying Liao; et al. (Poultry Science)
Duck hepatitis A virus (DHAV) causes an acute and severe infectious disease characterized by liver swelling and hemorrhage, predominantly affecting ducklings under three weeks of age. This disease leads to significant economic losses in the duck farming industry. In China, both DHAV1 and DHAV3 are prevalent, with DHAV3 being more dominant. Among the three structural proteins of DHAV, the VP1 protein is the most critical as it induces neutralizing antibody production, serves as the binding protein for viral adsorption to cell-specific receptors, and determines viral antigenicity. The serum neutralization (SN) test is the ''gold standard'' for evaluating DHAV vaccine-immune serum; however, it is time-consuming and labor-intensive. To address this limitation, we developed a rapid, sensitive, and specific blocking ELISA (bELISA) for detecting DHAV3 antibodies. This assay utilizes DHAV3 virus-like particles (VLPs) as the coating antigen and the VP1-specific monoclonal antibody 4B8 as the blocking antibody. The bELISA demonstrated high sensitivity and specificity, detecting only DHAV3 antibodies without cross-reactivity with DHAV1 or other viral antibodies. The assay's cutoff value was determined to be 38.21 %, with intra- and inter-batch coefficients of variation below 5 %, indicating excellent reproducibility. The bELISA showed a 100 % positive concordance rate and a 93.65 % negative concordance rate with the SN test, resulting in an overall concordance rate of 96 %. In summary, this study presents the development of a high-quality bELISA for the detection of DHAV3 antibodies. This assay is suitable for clinical diagnosis of DHAV3, evaluation of maternal antibody levels, and assessment of vaccine efficacy in ducklings, offering a valuable tool for disease control and prevention in the duck industry.